Structured testing model for object-oriented software development - Toh, Kee Heng. (2011)
In this dissertation* , we propose a structured testing model for object-oriented software development. Testing techniques used in traditional procedural software systems are studied and applied to the testing model. Object-oriented software makes use of concepts such as encapsulation, inheritance and polymorphism, making it fundamentally different from procedural software. Thus, our testing model examines what is required to adequately test object-oriented software. Existing techniques are adapted to provide the required level of testing adequacy, and new techniques are introduced if necessary. The object-oriented testing model consists of 3 levels of testing, namely. Class Testing, Subsystem Testing and Final System Testing. The various testing techniques are applied appropriately to each level of testing. In our dissertation, we also introduce a development process that integrates the testing activities into the iterative and incremental development lifecycle that is often associated with object-oriented software development. The work done in this dissertation is done in addition to a 420 hours Software Development Project. Both the dissertation and the software project partially fulfil the requirements for the Degree of Master of Science in Communication and Network Systems.